2019
DOI: 10.1103/physrevx.9.031044
|View full text |Cite
|
Sign up to set email alerts
|

Circumventing the Dephasing and Depletion Limits of Laser-Wakefield Acceleration

Abstract: Compact electron accelerators are paramount to next-generation synchrotron light sources and freeelectron lasers, as well as for advanced accelerators at the TeV energy frontier. Recent progress in laserplasma driven accelerators (LPA) has extended their electron energies to the multi-GeV range and improved beam stability for insertion devices. However, the subluminal group velocity of plasma waves limits the final electron energy that can be achieved in a single LPA accelerator stage, also known as the dephas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…This concept improves upon the chromatic flying focus [19] by providing the original features of a small focal spot that can propagate at any velocity over any distance, while using an achromatic focusing system to maintain a transformlimited pulse duration ideal for LWFA. The concept does not require (1) the plasma to be colocated with an active lasing media [26], (2) a structured plasma [27], or (3) multiple intersecting laser pulses [28]. In contrast to the pair of laser pulses with tilted pulse fronts employed in the traveling wave electron acceleration described by Debus et al [28], the axiparabola-echelon pair delivers a single laser pulse that can drive a cylindrically symmetric wakefield, preserving the favorable focusing fields and maintaining the strong electrostatic fields resulting from near spherical expulsion of electrons in the bubble regime.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This concept improves upon the chromatic flying focus [19] by providing the original features of a small focal spot that can propagate at any velocity over any distance, while using an achromatic focusing system to maintain a transformlimited pulse duration ideal for LWFA. The concept does not require (1) the plasma to be colocated with an active lasing media [26], (2) a structured plasma [27], or (3) multiple intersecting laser pulses [28]. In contrast to the pair of laser pulses with tilted pulse fronts employed in the traveling wave electron acceleration described by Debus et al [28], the axiparabola-echelon pair delivers a single laser pulse that can drive a cylindrically symmetric wakefield, preserving the favorable focusing fields and maintaining the strong electrostatic fields resulting from near spherical expulsion of electrons in the bubble regime.…”
mentioning
confidence: 99%
“…The concept does not require (1) the plasma to be colocated with an active lasing media [26], (2) a structured plasma [27], or (3) multiple intersecting laser pulses [28]. In contrast to the pair of laser pulses with tilted pulse fronts employed in the traveling wave electron acceleration described by Debus et al [28], the axiparabola-echelon pair delivers a single laser pulse that can drive a cylindrically symmetric wakefield, preserving the favorable focusing fields and maintaining the strong electrostatic fields resulting from near spherical expulsion of electrons in the bubble regime. Further, by adjusting the profile of the echelon, the ponderomotive force can be made to follow a dynamic trajectory, with either accelerations or decelerations to control trapping and reduce dark current.…”
mentioning
confidence: 99%
“…Figure 2 In this work, we run PIConGPU's Traveling Wave Electron Acceleration (TWEAC) and Laser Wakefield Acceleration (LWFA) simulations. A deeper dive into the science of the TWEAC and LWFA simulations is explained by Debus et al [13]. We profile the simulations using various state-of-the-art profiling tools and micro-kernel benchmarking suites.…”
Section: Picongpu a Plasma Physics Applicationmentioning
confidence: 99%
“…However, some of these methods demand sophisticated configurations, and the produced e beams are deficient in charge, energy spread, or peak energy, which hinder their practical applications. Recently, some significant studies have been reported to improve the specific qualities of e beams, including the peak energy [16][17][18][19][20], the energy spread [21][22][23][24][25][26], the brightness [24,27,28], the reproducibility [29][30][31], etc. More considerable research efforts, however, are still needed to focus on generating reproducible high-quality electrons for table-top light sources, which should have a broad-ranging impact across multiple scientific fields.…”
Section: Introductionmentioning
confidence: 99%